Beethoven - Rich, Richard; Brown, Jared F.; Nissen, Brian, 1939-; Nest Entertainment, Inc.; Rich Animation Studios (Coppell, TX : NEST Family Entertainment, 2005)
Animated biography of Beethoven.
"Interactive DVD packed with bonus features" -- Container.
Website access feature requires a computer with DVD drive and Internet access. Computer is not required for other DVD-video bonus features" -- Container.
Includes Resource & Activity Book.
Music, Lex De Azevedo.
DVD.
Includes Spanish language track with optional English or Spanish subtitles.
Keywords: Beethoven, Ludwig van, -- 1770-1827 -- Juvenile films; Beethoven, Ludwig van, -- 1770-1827.; Composers -- Germany -- Biography -- Juvenile films; Composers; z; Video recordings for children; Educational videos; Biographical (Nonfiction) -- Animation; Children's -- Animation